The Psycho-Grammatical Description of the Existential Locative “there” Constructions - Suvaryan, Armine (Armenian Folia Anglistika, 2009)
The article discusses problems related to the psycho-grammatical description of the existential locative “there” constructions. The research indicates that the psycho-grammatical processes not visible to the naked eye in a sentence at first glance, may have their specific expressions in discourse.